Experimental investigation of hotspot phenomenon in PV arrays under mismatch conditions. (15th March 2023) - Ghosh, Swatilekha; Singh, Santosh Kumar; Yadav, Vinod Kumar
Highlights: Reviews the looming global problem of PV waste generation in near future. Identifies issues in the PV modules which contribute to early failure. Two configurations are experimentally compared in light of PV reliability. Proposes ways to mitigate high-volume of PV waste due to early failures. The inclusion of bypass circuit verification test is recommended in IEC 61215. Abstract: The global installed capacity of photovoltaic (PV) plants is increasing exponentially since the beginning of the 21st century. And as the early installations have started nearing their end-of-life, presently, PV waste management has started raising concerns amongst environmental researchers. The cumulative PV waste generation is estimated to reach 8 million tonnes by 2030, however, interestingly, this humungous volume may be reduced by 79% if early failures could be averted. And one of the major contributors to the early failure of the PV modules is the hotspot generation under partial shading and other mismatch conditions. Various innovative array configurations have been proposed in the past to minimize power loss under partial shading conditions, however, the performance of those from the perspective of hotspot formation and PV reliability is neglected. In the present work, the efficacy of the hotspot prevention mechanism is investigated, both in an experimental setup and in real installations. The results revealed that the extant mechanism is ineffective in preventing the occurrence of hotspots in total cross-tied (TCT) array configuration, which is hailed as the best performing one in the literature, when studied from the perspective of mismatch power loss only.